Chemical constituents from the twigs of decaneuropsis vagans (asteraceae) and its chemotaxonomic study - Anuruk Chailungka (2019)
© 2019, Chiang Mai University. All rights reserved. The first phytochemical investigation of the twigs of Decaneuropsis vagans (DC.) H. Rob. & Skvarla. resulted in the isolation of six known compounds, including lupeol palmitate (1), lupeol acetate (2), eugenol (3), macelignan (4) and a mixture of β -sitosterol (5) and stigmasterol (6). Their structures were characterized by various spectroscopic methods and comparison with the data reported in the literature. Compounds 1-6 were isolated from this species for the first time and compound 4 was firstly found in the Asteraceae family.